Factors Affecting Firm’s Energy Efficiency and Environmental Performance: The Role of Environmental Management Accounting, Green Innovation and Environmental Proactivity - Jermsittiparsert, Kittisak; Somjai, Sudawan; Toopgajank, Sriparinya (International Journal of Energy Economics and Policy, 2020)
Environment degradation is a global issue for which every individual or entity has to play their role. For an organization there are several ways by which their contribution to the environment can be improved. For said purpose, the present study was conducted in which the role of green innovation, environment proactiveness and environment management accounting was studied on environment performance and energy efficiency. Moreover, to meet the goal, the present study employs quantitative research approach where data was collected from 367 respondents and PLS-SEM was employed. The results revealed significant impact of the aforementioned independent constructs on dependent variables. Based on the findings, recommendations were given whereas limitations and barriers of the research and guidelines for the future researches are also discussed. Keywords: Environmental Management Accounting; Green Innovation; Environmental Proactivity; Energy Efficiency; Environmental Performance JEL Classifications: O13, R11, O31 DOI: https://doi.org/10.32479/ijeep.9220